Cardiopulmonary monitoring in Thai ICUs (ICU-RESOURCE I Study) - Kaweesak Chittawatanarat (2018)
Objective: Cardiopulmonary monitoring (CPM) is rapidly progressing but data regarding CPM in Thai ICUs was unavailable. The objective of this study was to describe the situation, and gaps of CPM in Thai ICUs. Material and Method: Data were retrieved from the ICU-RESOURCE I study database survey. CPM was divided into two aspects of device and measurement methods. These were categorized by device availability grading (AG), device availability per bed (DPB) and numeric frequency grading scale (FGS). Device availability was compared between academic and nonacademic ICUs. Gap analysis of DPB and FGS was performed. Statistical significant difference was defined as p-value<0.05. Results: One hundred and fifty-five ICUs across Thailand participated in this study. Academic ICUs had significantly more devices available in new equipment with p<0.05 (Vigilio, PiCCO, NICOM, esophageal pressure monitoring, transcutaneous PO2, electrical impedance tomography of lung) as well as measurement methods (stroke volume variation [SVV], pulse pressure variation [PPC], central venous oxygen saturation [ScvO2], lung mechanics). Most of new and higher technological devices had low density and few were available in all of Thai ICUs. However, in gap analysis, although these new devices and measurement techniques were available in ICUs, they were not frequently utilized. Conclusion: New technology devices of CPM had more availability in ACAD than in non-ACAD ICUs. Formal continuous training in new measurement methods should be established for reducing the availability and utilization gap (Thai Clinical Trial Registry: TCTR-201200005).